The Other Side of Ecology: thinking about the human bias in our ecological analyses for biodiversity conservation - Lopes, Sergio de Faria (Ethnobiology and Conservation, 2017)
Ecology as a science emerged within a classic Cartesian positivist context, in which relationships should be understood by the division of knowledge and its subsequent generalization. Overtime, ecology has addressed many questions, from the processes that lead to the origin and maintenance of life to modern theories of trophic webs and non equilibrium. However, the ecological models and ecosystem theories used in the field of ecology have had difficulty integrating man into analysis, although humans have emerged as a global force that is transforming the entirety of planet. In this sense, currently, advances in the field of the ecology that develop outside of research centers is under the spotlight for social, political, economic and environmental goals, mainly due the environmental crisis resulting from overexploitation of natural resources and habitat fragmentation. Herein a brief historical review of ecology as science and humankind’s relationship with nature is presented, with the objective of assessing the impartiality and neutrality of scientific research and new possibilities of understanding and consolidating knowledge, specifically local ecological knowledge. Moreover, and in a contemporary way, the human being presence in environmental relationships, both as a study object, as well as an observer, proposer of interpretation routes and discussion, requires new possibilities. Among these proposals, the human bias in studies of the biodiversity conservation emerges as the other side of ecology, integrating scientific knowledge with local ecological knowledge and converging with the idea of complexity in the relationships of humans with the environment.